Formulation and stability of Ulva lactuca fatty acid oil in water (O/W) microemulsion - Ningrum, Y. P.; Budhiyanti, S. A. (Rynnye Lyan Resources, 2022)
The research was conducted to produce stable oil in water microemulsion (O/W) of Ulva lactuca fatty acid. Ulva lactuca green algae samples were taken from Ngandong Beach, Gunungkidul. This research consisted of several stages, including the extraction of U. lactuca fatty acids, and microemulsion formulations made of U. lactuca fatty acid microemulsions. The tests carried out include turbidity index, heating, centrifugation, electrical conductivity, and peroxide value. Ulva lactuca fatty acid extraction was carried out using ethanol-hexane at 70°C for 3 hrs, and then the extract was stored in the freezer until used. Microemulsion formulation was made of variations of Tween 80, Span 80, and Tween 20 surfactants with 0 to 90% water content at 70°C. All formulas were then tested for heating, centrifugation, turbidity index, and electrical conductivity. The results showed that stable oil in water microemulsions was the sample with a water content of 70, 80, and 90% of each formula. The stabilized microemulsions were added with U. lactuca extract with 100, 200, and 300 ppm concentrations, then tested for centrifugation, heating, and turbidity index. The most stable formula was tested for peroxide value. The two microemulsions with the best results were the formula of A2-200 (Tween 80: Span 80: Tween 20 = 92: 5.5: 2.5, v/v) and C2-200 (Tween 80: Span 80: Tween 20 = 87: 5.5: 7.5, v/v) with 80% water content and 200 ppm of U. lactuca fatty acid extract.